THE EFFECTIVENESS OF BUTTERFLY PEA (CLITORIA TERNATEA) TEA CONSUMPTION IN REDUCING BLOOD PRESSURE AMONG ELDERLY PATIENTS WITH HYPERTENSION - Nasution, Sri; Pane, Halimah Fitriani; Salsabila, Sifa (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Hypertension is one of the major health problems among the elderly, which poses a high risk of cardiovascular complications. Non-pharmacological interventions such as the consumption of butterfly pea tea ( Clitoria ternatea ) are considered to have potential in lowering blood pressure. This study aimed to examine the effectiveness of butterfly pea tea in reducing blood pressure among elderly patients with hypertension at the Posyandu Lansia in Mabar. This research employed a pre-experimental design with a one-group pretest-posttest approach. A total of 30 elderly respondents with hypertension participated in the study and were given 200 ml of butterfly pea tea daily for seven consecutive days. Blood pressure measurements were taken before and after the intervention and analyzed using the paired t-test . The results revealed a significant decrease in both systolic and diastolic blood pressure. The average systolic pressure decreased by 13.0 mmHg, from 152.3 mmHg to 139.3 mmHg, while the diastolic pressure decreased by 8.03 mmHg, from 93.3 mmHg to 85.27 mmHg. Statistical analysis showed a p-value of 0.000 (p < 0.05), indicating that butterfly pea tea is effective in reducing blood pressure among elderly patients with hypertension.